Moral Paradigms of Intergenerational Solidarity in the Coronavirus-Pandemic - Ellerich-Groppe, Niklas; Steckdaub-Muller, Irmgard; Pfaller, Larissa; Schweda, Mark (Analyse und Kritik, 2024)
Solidarity between generations served as a prominent but controversially discussed normative reference point in public debates about the Coronavirus-pandemic. The aim of this contribution is the empirical reconstruction and ethical evaluation of prominent notions of intergenerational solidarity and their underlying assumptions in the public media discourse on the pandemic in Germany. After a brief introduction to the concept of intergenerational solidarity and the pertinent discourses during the pandemic, we present the results of a comprehensive qualitative content analysis of 149 articles from leading media in Germany. On this basis, we carve out three typical understandings of intergenerational solidarity: (a) communal care, (b) mutual support, and (c) responsible use of freedom. We discuss these understandings and the underlying 'moral paradigms' and evaluate their theoretical and practical implications from an ethical point of view, drawing conclusions for discourses on future societal crises.
CRIS-Team Scopus Importer:2024-06-07
Keywords: ethical analysis; generation; intergenerational relations; media debate; public discourse; solidarity